2017
DOI: 10.1021/acs.joc.7b00959
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Spirocyclic Amines by Using Dipolar Cycloadditions of Nitrones

Abstract: Aliphatic ketones containing a chloride and alkene were heated with hydroxylamine to promote cascade, tandem condensation to oximes, cyclization to nitrones, and 1,3-dipolar cycloaddition to tricyclic isoxazolidines as single stereoisomers. Single regioisomers were obtained when three atoms linked the ketone and dipolarophile to give five-membered rings but mixtures resulted with four atoms in the tether unless a terminal ester was located on the alkene. The N-O bond in the products could be reduced to give sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…The ketone 1 was prepared in a single step by addition of 4-pentenylmagnesium bromide to 4-chlorobutanoyl chloride according to the literature. 24 Heating this ketone with glycine methyl ester gave the desired tricyclic product 3 as a single stereoisomer (Scheme 2). We found that the The stereochemistry of the product 3 was determined by reduction of the ester to give the alcohol 4, followed by acylation to give the ester 5 (Scheme 3).…”
Section: Scheme 1 Cascade Condensation Cyclization Cycloaddition Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…The ketone 1 was prepared in a single step by addition of 4-pentenylmagnesium bromide to 4-chlorobutanoyl chloride according to the literature. 24 Heating this ketone with glycine methyl ester gave the desired tricyclic product 3 as a single stereoisomer (Scheme 2). We found that the The stereochemistry of the product 3 was determined by reduction of the ester to give the alcohol 4, followed by acylation to give the ester 5 (Scheme 3).…”
Section: Scheme 1 Cascade Condensation Cyclization Cycloaddition Ofmentioning
confidence: 99%
“…In contrast to the ketone 1, the ketone 8 (prepared as reported in the literature) 24 allowed successful condensation, cyclization, cycloaddition with glycine to give the product 9 (Scheme 5). This reaction required switching to the solvent DMF, as the use of toluene gave only recovered ketone 8.…”
Section: Scheme 4 Synthesis Of the Ketone 6 And Cycloadductmentioning
confidence: 99%
See 1 more Smart Citation
“…We have reported a number of examples of the formation of polycyclic amines by use of a cascade strategy that incorporates a condensation reaction of an amine and an aldehyde (or ketone) followed by in situ cyclization of the imine (or oxime or hydrazone) on to an alkyl halide, followed by in situ dipolar cycloaddition. [10][11][12][13][14][15] Our efforts have been centred mostly on fused ring systems (Scheme 1a) and this chemistry leads to the synthesis of several natural products (aspidosperma alkaloids, myrioxazine A). [10][11] An intermolecular cycloaddition alternatively leads to bicyclic products and has been used to prepare crispine A and macronecine.…”
mentioning
confidence: 99%
“…12 We have extended the methodology to bridged polycyclic compounds (Scheme 1b), 13 and recently to spirocyclic compounds (Scheme 1c). 14 The research on the bridged compounds located the branch point (between the alkene dipolarophile and the alkyl halide) β-to the aldehyde. This led to compounds with a onecarbon bridge.…”
mentioning
confidence: 99%